2021
DOI: 10.1108/ils-10-2020-0234
|View full text |Cite
|
Sign up to set email alerts
|

Authenticity perceptions in virtual environments

Abstract: Purpose This paper aims to examine three distinct aspects of authenticity that pre-service teachers (PSTs) experience when they engage with virtual classroom environments to develop their content-intensive instructional practice – task authenticity, student avatar authenticity and performance authenticity – and their perceptions about the usefulness of the simulated teaching experience to support their learning. Design/methodology/approach This paper explored these conceptions of authenticity and usefulness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Any simulation sacrifices some degree of authenticity in order to reduce complexity [ 12 ]. The key for simulations is to have enough authenticity for the task to be considered beneficial practice [ 58 ]. The results from the PST survey indicate that a majority of the PSTs believe ELK is authentic, and that they felt the activity met the goals of practicing eliciting learner knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Any simulation sacrifices some degree of authenticity in order to reduce complexity [ 12 ]. The key for simulations is to have enough authenticity for the task to be considered beneficial practice [ 58 ]. The results from the PST survey indicate that a majority of the PSTs believe ELK is authentic, and that they felt the activity met the goals of practicing eliciting learner knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…There are two main components of the task: (1) the materials that are provided to the teacher facilitating the discussion, and (2) the materials that are provided to the simulation specialist during their training about how to enact the students' ideas during the discussion. Previous research has suggested that participants perceive the students' responses and the performance task to be authentic representations of how students at this grade level respond and what teachers are asked to engage in during science instruction (Mikeska & Howell, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding simulations, the experience of presence through authenticity and involvement plays a key role and positively affects performance and learning outcomes (Grossman et al, 2009;Schubert et al, 2001). Prior research on presence has shown positive effects on students' learning outcomes (Chernikova, et al, 2020a(Chernikova, et al, , 2020bMikeska & Howell, 2021;Stevens & Kincaid, 2015). In particular, little research has been conducted on understanding learner characteristics that might serve as more or less favorable capacities for experiencing a digital learning environment as authentic.…”
Section: Situative Learning Experiences During Video-based Simulationsmentioning
confidence: 99%
“…Incorporating videos into teacher education and professional development can ensure that both of these criteria are met (Borko et al, 2008 ; Codreanu et al, 2020 ; Santagata, 2009 ). Although which learning environment and which learner characteristics increase the perception of authenticity has yet to be determined by research (Betz, 2018 ; Betz et al, 2016 ; Gulikers et al, 2005 ; Mikeska & Howell, 2021 ), videos have been proven reliable in preserving the authenticity of snippets of everyday teaching and learning (Gaudin & Chaliès, 2015 ; Kang & van Es, 2019 ; Tekkumru-Kisa & Stein, 2017 ). At the same time, the practice of selecting distinct situations, segmenting them into meaningful learning units, and highlighting particularly relevant situations in staged videos offers many technical opportunities for a sufficient decomposition of complex classroom realities (Derry et al, 2014 ; Thiel et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%